Proximal femur sarcomas with intra‐articular disease—Do intra‐articular resections provide adequate local control?. Issue 8 (25th August 2020) - Nayak, Prakash; Gupta, Srinath; Patil, Akshay; Gulia, Ashish; Puri, Ajay
Abstract: Background and Objectives: Hip preserving (intra‐articular) resections for proximal femur sarcoma have better function compared to peri‐acetabular (extra‐articular) resections, which are more complex and morbid. But, do intra‐articular resections in selected cases with intra‐articular disease provide adequate local control? Method: Extra‐articular resection or intra‐articular resection in cases without pathologic fracture or away from joint/capsule was classified as a planned safe margin (SM). Circumferential removal of labrum without acetabular resection in cases without gross joint contamination was classified as planned close margins (CM). We analyzed local recurrence‐free survival (LRFS) (death as a competing event) for 86 proximal femur resections (SM = 55, CM = 31). Results: The 5 years LRFS was 84% (n = 6/55, 10%) in the SM group and 67% (n = 4/31, 12%) in the CM group. There was no worsening of local recurrence (LR) in the CM group (subdistribution hazard [sH] = 0.69; 95% confidence interval [CI], 0.21‐2.29; P  = .56). Poor chemotherapy‐induced necrosis predicted worse LR (sH = 0.1; 95% CI, 0.01‐0.8; P  = .03). Overall survival was 16% (SE 8%) at 5 years with LR vs 64% (SE 7%) without LR ( P  = .0076). Conclusion: In proximal femur sarcomas with potential for involvement of the hip joint, a CM in selected cases did not worsen LR; providing an option for avoiding additional morbidity with extra‐articular resections.